Woodchip bioreactors provide sustained denitrification of brine from groundwater desalination plants. (1st July 2021) - Díaz-García, Carolina; Martínez-Sánchez, Juan J.; Maxwell, Bryan M.; Franco, José Antonio; Álvarez-Rogel, José
Abstract: Woodchip bioreactors are widely known as a best management practice to reduce excess nitrate loads that are discharged with agricultural leachates. The aim of this study was to evaluate the performance of citrus woodchip bioreactors for denitrification of brine (electrical conductivity ≈ 17 mS cm −1 ) from groundwater desalination plants with high nitrate content (NO3 − -N ≈ 48 mg L −1 ) in the Campo de Cartagena agricultural watershed, one of the main providers of horticultural products in Europe. The performance was evaluated relative to seasonal changes in temperature, dissolved organic carbon (DOC) provided by woodchips, hydraulic residence time (HRT) and woodchip aging. Bioreactors (capacity 1 m 3 ) operated for 2.5 years (121 weeks) in batch mode (24 h HRT) with three batches per week. Denitrification efficiency was modulated by DOC concentration, temperature, hydraulic residence time and the drying-rewetting cycles. High salinity of brine did not prevent nitrate removal from occurring. The high DOC availability (>25 mg C L −1 ) during the first ≈48 weeks resulted in high nitrate removal rate (>75%) and nitrate removal efficiency (until ≈ 25 g N m −3 d −1 ) regardless of temperature. Moreover, the high DOC contents in the effluents during this period may present environmental drawbacks. Denitrification was still high after 2.5 years (reaching ≈9.3 g N m −3 d −1 in week 121), but dependence on warm temperature became more apparent with woodchips aging from week ≈49 onwards. Nitrate removal efficiency was highest on the first weekly batch, immediately after woodchips had been unsaturated for four days. It was attributable to a flush of DOC produced by aerobic microbial metabolism during drying that stimulated denitrification following re-saturation. Hence, alternance of drying-rewetting cycles is an operation practice that increase bioreactors nitrate removal performance. Graphical abstract: Image 1 Highlights: Citrus woodchips effectively denitrify high-nitrate concentration brine. Citrus woodchip bioreactors provide enough organic carbon for the denitrification. Drying-rewetting cycles improve denitrification due to aerobic conditions. DOC, temperature and HRT had an effect on denitrification efficiency. Evolution woodchips from a two-year-old denitrifying bioreactor were evaluated.